Descrição da fauna parasitária de raias e tubarões marinhos (Elasmobranchii), fauna acompanhante da pesca comercial no litoral Sul e Sudeste do Brasil - Napoleão, Silvia Roselli [UNESP] (2014)
The main objective of this study was to determine the diversity of parasites in marine sharks and rays in the south and southeast coast of Brazil, catches by pair trawls and by bottom trawling of small and medium size– for fishery of shrimp Xiphopenaeus kroyeri and Penaeus brasiliensis, respectively, and landed in the cities of Santos and Guaruja - SP . Between april 2012 and april 2013, fourteen species of stingrays and three species of sharks, totaling 129 animals, were necropsied: 7 sharks and 116 rays. As a result, refers reoccurrence of nematode Proleptus acutus in Atlantoraja platana , Rhinobatos percellens, Rhinobatos horkelli, Zapteryx brevirotris, Rioraja agassizii and Atlatoraja cyclophora, recurrence of Procamallanus (Spirocamallanus) pereirae in Atlantoraja castenaui and Atlatoraja cyclophora, and recurrence the Cestoda Rhinoptericola megacantha in Rhinoptera brasiliensis . It refers also occurrence of six different species of cestodes, not yet recorded: two of the species found (Cestoda sp. gen. 1 and Cestoda gen. sp. 2) belong to genera not yet described in the literature . The other cestodes were identified only at genus level (Rhodobothrium sp., Cairaeanthum sp., Uncibilocularis sp. and Tiarabothrium sp.), because it does not characterize the species already described them